The effect of advertising attractiveness, influencer marketing, online customer review, and brand image on purchase decision Somethinc - Firnanda, Alifiya Ayu; Krisnawati, Wenti (Enrichment : Journal of Management, 2023)
The study analyzes the effect of Advertising attractiveness, Influencer Marketing, Online Customer Review, and Brand Image. They are using quantitative research with 100 respondents—the sampling technique of this research with purposive sampling. Primary data on this study was obtained from the dissemination of questionnaires online. The sample in this study is a student of Muhammadiyah University of Greece who is or has used and has made a purchase at least once on Somethinc products. The sampling is using non-probability sampling techniques. The data is processed using IBM SPSS Statistic 24. In this study, there was a positive and significant influence between the variables of Advertising attractiveness, Influencer Marketing, Online Customer Review, and Brand Image on the Purchase Decision of Somethinc products. If you see the double linear regression analysis result on the determination coefficient (R2), the result is adjusted R square = 0.611. It showed that purchasing decisions could be influenced by variables such as Advertising Attractiveness, Influencer Marketing, Online Customer Review, and Brand Image by 61%. In comparison, the remaining 39% were affected by other factors not found in this study